High casein concentration induces diarrhea through mTOR signal pathway inhibition in post-weaning piglets - Gao, Jing; Ma, Li; Yin, Yulong; Chen, Yongzhong; Li, Tiejun (Frontiers in Microbiology, 2024)
Post-weaning diarrhea is one of the major health problems that is accompanied by serious morbidity and mortality in the pig industry. Previous studies have demonstrated that both protein source and concentration are closely associated with post-weaning diarrhea in piglets. Our study was conducted to prevent and control post-weaning diarrhea by choosing different dietary protein concentrations. To avoid influences from other protein sources, casein was used as the only protein source in this study. Fourteen piglets (8.43 ± 0.3 kg, weaned at 28d) were randomly allotted to two dietary protein groups: a lower casein group (LP, containing 17% casein) and a high casein group (HP, containing 30% casein). The experiment lasted for two weeks, and all piglets were free to eat and drink water ad libitum. The diarrhea score (1 = normal; 3 = watery diarrhea) and growth performance were recorded daily. The results showed that the piglets in the HP group had persistent diarrhea during the whole study, but no diarrhea was noticed in the control groups. The body weights and feed intake were significantly decreased in the HP piglets when compared with the LP group (P < 0.05). The gastrointestinal pH was significantly increased in the HP group compared with the LP group (P < 0.05). The microorganisms of two groups were significantly affected by the protein concentration of the diet. High casein diet significantly reduced microbiota diversity, and 30% casein diet decreased the abundance of Firmicutes, Bacteroidetes and Actinobacteria at the phylum, while reduced the relative abundance of Ruminococcus at the genus level compared to LP group. in the intestine of piglet. The diarrhea-related mRNA abundances were analyzed by real-time PCR, and the results showed that HP treatment markedly decreased the expression of solute carrier (SLC, P <0.05). The mammalian target of rapamycin (mTOR) signaling pathway (P < 0.01) was 2 activated in the HP group. In conclusion, a high protein concentration diet induced postweaning diarrhea with decreased growth performance, increased gastrointestinal pH, and reduced expression of solute carrier proteins. However, the relationship between high dietary casein feed and post-weaning diarrhea stays unclear.